OPTIMASI BERBAGAI TEPUNG KANJI PADA NUGET IKAN PATIN TERHADAP KARAKTERISTIK SENSORI DENGAN METODE PERMUKAAN RESPONS - Desmelati Desmelati (Jurnal Floratek, 2008)
Optimization of Several Tapioca Flours in Patin Fish Nuget on Sensory Characteristic Through Response Surface Method Desmelati1 dan Rita Hayati 2 1Staf Pengajar UNRI, Pekanbaru2Staf Pengajar Unsyiah, Darussalam Nanggroe Aceh Darussalam ABSTRACT Result of the study showed that optimum region for nugget production using wheat flour, tapioca flour and corn flour were 1.3 – 10.54%, 1.98 – 4.30%, and 1.18 –11.89%, respectively.  Three formulations were selected for validation study.  Two formulation were from acceptance region (F1=0.37 of wheat flour, 0.46 tapioca flour, 0.17 corn flour, F2 =0.37 of wheat flour, 0.40 tapioca flour, 0.22 corn flour), and one formulation from rejection region (F3 =12.5 of wheat flour, 75 tapioca flour, and 12.5 corn flour). The validation of the three optimum points using sensory evaluation showed that formulation F1 was most acceptable followed by F2 and F3. There was significant difference (P≤0.05) between F1 and F2 when compared to F3, thus model equation was able to predict the optimum points.